2021
DOI: 10.1002/mar.21500
|View full text |Cite
|
Sign up to set email alerts
|

How does public recognition affect price sensitivity to green products? The role of self‐construal and temporal distance

Abstract: This study focused on the role of public recognition in fostering lower levels of price sensitivity to green products and the factors that influence this relationship. We conducted three studies to analyze the relationship between public recognition and price sensitivity to green products and the moderating effects of self-construal and temporal distance on this relationship. A total of 865 persons took part in the research. Study 1 found that public recognition significantly reduces price sensitivity to green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…Consumer research scholars increasingly draw on construal‐level theory to explain consumers' perception, evaluation, prediction, and decision‐making (Adler & Sarstedt, 2021; Filieri et al, 2023; Gao et al, 2021). Gao et al (2021) focus on construal level theory (CLT) and temporal distance and demonstrate that temporal distance can influence consumers' price sensitivity for green products.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer research scholars increasingly draw on construal‐level theory to explain consumers' perception, evaluation, prediction, and decision‐making (Adler & Sarstedt, 2021; Filieri et al, 2023; Gao et al, 2021). Gao et al (2021) focus on construal level theory (CLT) and temporal distance and demonstrate that temporal distance can influence consumers' price sensitivity for green products.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Consumer research scholars increasingly draw on construal‐level theory to explain consumers' perception, evaluation, prediction, and decision‐making (Adler & Sarstedt, 2021; Filieri et al, 2023; Gao et al, 2021). Gao et al (2021) focus on construal level theory (CLT) and temporal distance and demonstrate that temporal distance can influence consumers' price sensitivity for green products. Adler and Sarstedt (2021) conducted a bibliometric analysis of research based on CLT and showed that CLT's relevance for consumer research has amplified, and its applications have been expanded to areas such as climate change and sustainability.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Social norms arised from the expectation of others' behavior and the consequences of abiding by or deviating from these norms, meta-analysis showed that social norms can promote behavior conducive to the environment (Perry et al, 2021). Gao et al (2021) analyzed the relationship between public awareness of green products and price sensitivity, and results showed that public recognition, self-explanation and time distance played an important role in predicting the price sensitivity of green products. Yan et al (2021a) discussed how the psychological feeling of power affects consumers' preference for green products, and found that the influence of power on green consumption is more prominent among the people with high green consumption value.…”
Section: Literature Co-citation Analysis and Knowledge Base Identific...mentioning
confidence: 99%
“…The distinction between analytical thinking (a characteristic of independent self-construal) and holistic thinking (a characteristic of interdependent self-construal) may be especially helpful in predicting consumer behavior (Gao et al, 2021). Previous studies have found that analytical thinkers view product and display content as separate data blocks (Zhu and Meyers-Levy, 2009).…”
Section: Self-construal Type As a Moderatormentioning
confidence: 99%
“…Interdependent self-construers attach importance to social connection with others and consider social norms rather than personal attitudes before making decisions (Hellmann et al, 2021). Friends' attitudes and opinions are important to them (Gao et al, 2021). Therefore, social experience plays a considerable role in the decision-making process of interdependent self-construers.…”
Section: Self-construal Type As a Moderatormentioning
confidence: 99%